2019
DOI: 10.3926/jotse.435
|View full text |Cite
|
Sign up to set email alerts
|

The flipped learning model in online based education for secondary teachers

Abstract: The online-based model known as “flipped learning” raises new challenges that are different from those of face-to-face teaching. The flipped learning model enhances the active and autonomous learning of students, changes the relationships between them and with the teacher, and encourages innovation within the learning process. The following paper presents a descriptive, poll-based study after having implemented the model in the Curricular design course offered in two different departments, Mathematics and Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…These findings are consistent with Romero-García et al [ 92 ], who found that the authors’ flipped learning model resulted in higher student satisfaction and academic performance. This underscores the value of innovative teaching methods in promoting positive student outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with Romero-García et al [ 92 ], who found that the authors’ flipped learning model resulted in higher student satisfaction and academic performance. This underscores the value of innovative teaching methods in promoting positive student outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…h. Flipped Classroom (kelas terbalik) Kelas terbalik (flipped classroom) adalah pembelajaran campuran, dimana materi pelajaran dipelajari secara praktis sebelum peserta didik hadir di dalam kelas. Dengan cara ini, kelas menjadi aktif sebagai ruang belajar, di mana materi yang telah dipelajari dikerjakan dan kegiatan pemecahan masalah juga dipraktekkan, proyek dan diskusi kelompok dilakukan, dengan dukungan dari pendidik dan kerjasama teman sejawat (Romero et al, 2019). Prinsip dasar dalam melaksanakan pembelajaran dengan metode kelas terbalik (flipped classroom) yaitu: (1) kegiatan kelas melibatkan sejumlah besar aktivitas peserta didik, belajar untuk bertanya, memecahkan masalah dan kegiatan lainnya, menuntut peserta didik untuk mengambil, menerapkan dan memperluas materi yang dipelajari secara online/mandiri; (2) peserta didik menerima umpan balik segera setelah kegiatan belajar di dalam kelas;…”
Section: G Pembelajaran Campuran (Blended Learning)unclassified
“…This study portrayed that tracing learning resources, making presentation files, and discussing them facilitated the students a lot in training their critical thinking. Moreover, McLean, Attardi, Faden, & Goldszmidt (2016) showed that flipped classrooms produced better learning processes and academic performance (Romero-García, Buzón-García, & Touron, 2018).…”
Section: Resultsmentioning
confidence: 99%